Original research The Efficacy & Safety of 0. 3% Acetylcysteine eyedrops in Filamentary keratitis - Irfan, Sameera (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine the safety and efficacy of 0. 3% Acetylcysteine eyedrops for the resolution of symptoms and signs of filamentary keratitis. Study design:A Randomised Clinical Trial (RCT). Place & Duration of study:This study was conducted at a tertiary care centre for a period of two and a half years, from April 2016toOctober 2018. Method:This was a prospective,interventionalstudy in which 52 consecutive cases (104 eyes) with mild to severe filamentary keratitis (classification criteria given below), between the ages of 9-72 years(mean 49±8.6) were included. Cases with an active ocular surface infection, uveitis, recent ocular surgery (< one month) and pregnant / lactating patients were excluded.All cases were prescribed lubricants, anti-inflammatory therapy (Tacrolimus skin cream 0.03%) and tetracycline eye ointment for the MGD. The alternate cases were divided into two equal groups of 26 cases; Group A received acetylcysteine eyedrops 0.3%, four times daily, Group B cases received placebo eyedrops (distilled water in a bottle).Clinical symptoms (OSDI),corneal filaments, corneal fluorescein staining,Tear Film BUT and Schirmer’s test were recorded at the beginning of study,and everytwo weeks,for the next 12 weeks. Results: Primary Outcome Measure was a reduction of symptoms (OSDI score) and absence of filament formation after treatment with 0.3% Acetylcysteine eyedrops. The patients were followed-up for a mean duration 12 ± 2weeks. There was a marked subjective as well as objective improvement in all cases within 2-4 weeks of therapy with Acetylcysteine 0.3% eyedrops as compared to the placebo group. Conclusion:Acetylcysteine 0.3% eyedrops efficiently dissolve filaments and offer quick resolution of symptoms even in severe cases of filamentary keratitis.